2008
DOI: 10.1021/ie701711v
|View full text |Cite
|
Sign up to set email alerts
|

Use of “Bricks and Mortar” Model To Predict Transdermal Permeation: Model Development and Initial Validation

Abstract: Presented in this paper is a general purpose computer model for predicting transdermal permeation of solutes in vivo. The “bricks and mortar” model is employed to represent the stratum corneum (SC), the main barrier to transdermal permeation. Transdermal permeation and absorption is modeled as a dynamic process of mass transfer in the heterogeneous stratum corneum including both the tortuous lipid pathway and the transcellular corneocytes pathway. The partition and diffusion properties of solutes in SC lipid m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 50 publications
0
45
0
Order By: Relevance
“…Wang et al (11,12) reported a more predictive two-dimensional model, in which the diffusion and partition coefficients were obtained from fundamental principles, and only the trans-bilayer mass transfer coefficient was fitted to deduce a correlation with the molecular weight. A similar two-dimensional approach was taken by Lian and coworkers (13,14), where data-fitting was only used to derive a correlation for calculating the diffusion coefficient in corneocytes, and the prediction accuracy was significantly improved when compared with the Wang's model in (11,12). With consideration of the two-dimensional microscopic skin structure, both models (11,12,13,14) demonstrated the importance of the trans-cellular diffusion pathway through the stratum corneum.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Wang et al (11,12) reported a more predictive two-dimensional model, in which the diffusion and partition coefficients were obtained from fundamental principles, and only the trans-bilayer mass transfer coefficient was fitted to deduce a correlation with the molecular weight. A similar two-dimensional approach was taken by Lian and coworkers (13,14), where data-fitting was only used to derive a correlation for calculating the diffusion coefficient in corneocytes, and the prediction accuracy was significantly improved when compared with the Wang's model in (11,12). With consideration of the two-dimensional microscopic skin structure, both models (11,12,13,14) demonstrated the importance of the trans-cellular diffusion pathway through the stratum corneum.…”
Section: Introductionmentioning
confidence: 99%
“…A similar two-dimensional approach was taken by Lian and coworkers (13,14), where data-fitting was only used to derive a correlation for calculating the diffusion coefficient in corneocytes, and the prediction accuracy was significantly improved when compared with the Wang's model in (11,12). With consideration of the two-dimensional microscopic skin structure, both models (11,12,13,14) demonstrated the importance of the trans-cellular diffusion pathway through the stratum corneum. In a later study, Lian and co-workers extended their model to include viable epidermis and dermis whilst maintaining the predictive capability (15).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations